2014
DOI: 10.3390/ijerph110100671
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Protective Motivation Theory (PMT) to Adolescents’ Drug Use Intention

Abstract: Early onset and increasing proliferation of illicit adolescent drug-use poses a global health concern. This study aimed to examine the correlation between Protective Motivation Theory (PMT) measures and the intention to use drugs among adolescents. An exploratory quantitative correlation design and convenience sampling were adopted. A total of 318 students completed a self-reported questionnaire that solicited information related to their demographics and activities, measures of threat appraisal and coping app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A study initiated by the World Bank also concludes that for China, more than 50% of the disease burden increase due to chronic diseases can be controlled by adjusting health‐risk behaviors . At present, many studies on health behaviors conducted in academia, involving women, adolescents, college students, elderly people, and corresponding factors, have further confirmed the importance of health behaviors to individual health and laid the foundation for the development of this study.…”
Section: Introductionmentioning
confidence: 54%
“…A study initiated by the World Bank also concludes that for China, more than 50% of the disease burden increase due to chronic diseases can be controlled by adjusting health‐risk behaviors . At present, many studies on health behaviors conducted in academia, involving women, adolescents, college students, elderly people, and corresponding factors, have further confirmed the importance of health behaviors to individual health and laid the foundation for the development of this study.…”
Section: Introductionmentioning
confidence: 54%
“…Another qualitative study was conducted among Chinese residents in the United Kingdom and the Netherlands by Jiang et al (2009) to identify the origins of SARS risk perceptions and their impact on precautionary actions and adverse consequences from the perspective of vulnerable communities living in unaffected regions, using protection motivation theory, and showed that perceived threat and perceived response efficacy regarding the SARS preventive behavior was the most important predictor. Another exploratory study for the correlation between Protection Motivation Theory measures and the intention to use drugs indicated that intrinsic and extrinsic reward components of the PMT explained about 50% of the variation, with odds ratios of 2.90 and 8.04 (p < .05) (Wu et al, 2014).…”
Section: Protection Motivation Theory (Pmt)mentioning
confidence: 99%
“…Although the PMT has been successfully applied in a wide range of health behavior interpretations and predictions [ 7 , 14 ], its application in studies on PHRs is still rather limited. Therefore, the present study incorporated the antecedent variables of the PMT as factors affecting the acceptance of PHRs.…”
Section: Introductionmentioning
confidence: 99%